Allogeneic pluripotent stem cells suppress airway inflammation in murine model of acute asthma - FİLİNTE, DENİZ; ÖĞÜLÜR, İSMAİL; AKKOÇ, TUNÇ (ELSEVIER, 2014)
New strategies are needed to suppress airway inflammation and prevent or reverse airway remodeling in asthma. Reprogramming induced pluripotent stem cells (iPSCs) have the potential of embryonic stem cells (ESCs) and provide a resource for stem cell-based utility. The aim of this study was to evaluate the histopathological and immunomodulatory effects of ESCs and iPSCs for potential allogenic application in a murine model of acute asthma. BALB/c mice were sensitized with alum-absorbed ovalbumin (OVA) and then challenged with 1% aerosolized OVA. 5 x 10(5) ESCs and iPSCs were administrated intranasally on the last day of nebulization. Mice were sacrificed after 24 h, and serum allergen specific antibody level, airway remodeling, cytokine levels in lung supernatants, and eosinophilic infiltration in BAL fluid were examined. As a result, more ESCs and iPSCs integrated into the lungs of mice in OVA groups than those of the controls. Epithelial, smooth muscle and basal membrane thicknesses as well as goblet cell hyperplasia occurring in airway remodeling were significantly suppressed by pluripotent stem cells in both distal and proximal airways. Percentage of eosinophils decreased significantly in BAL fluid as well as serum allergen-specific IgE and IL-4 levels in lung supernatants. On the contrary, regulatory cytokine - IL-10 level - was enhanced. Application of especially ESCs significantly increased the percentage of Treg subsets. Our comparative results showed that i.n. delivery of miRNA-based reprogrammed iPSCs is beneficial in attenuating airway inflammation in a murine model of acute asthma, and that cells also have similar immunomodulatory effects in mice. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Acute asthma murine model; BALB/c; ESCs; iPSCs; OVA; BRONCHIAL HYPERRESPONSIVENESS; T-CELL; MOUSE; DIFFERENTIATION; PREVALENCE